Menuju Integrasi Peng awasan Pupuk Bersubsidi: Sebuah Rancang Bangun Prototipe E-Suplay Chain Management - Hari Sunarto (Jurnal Manajemen, 2014)
Misappropiation of subsidized  fertilizer is one  source  of disturbance  factors that may lead to scarcity of fertilizer supply to farmer and ultimately  disturb to national food  security  program.  Along  with this,  there are many other sources  of disturbance  in achieving  high standard  of key performance indicators, namely,  6-precision  - precise in fertilizer  types,   volume,  place,  time,  quality  and  price.  It  is  a  need  to  minimize disturbances by  supervision.   By  law,  fertilizer and  pestiside  supervisory   committees (KP3) at national,  provicial  and district level asigned to supervice  fertilizer acquisition, distribution   and  usage  by  farmers.  Under  the  frame  of thinking  an  e-supply  chain management and  management control  system,  the KP3 remains  head  on some  issues, among  others  (a)  not  refer to  Regulation  60/2008  on  the  System  of Internal  Control Government,  (b) fragmented  business processses  in reporting,  (c) in this digital age still relies on written  (paperworks)    reports. Triangulation  research  method  is being used in longitudinal  study at a time span 2008-2013 to identify the real needs of KP3 then to set up  an    appropriate   prototype   of   application  software.  The  software   integrates  the business   process   among   authorities  and  it  works  online,  During  the   focus  group discussion,  KP3  appreciated  these  efforts.  Knowingly  finalization  process  is  still long way  to  go,  because   it needs  to  build  information  technology   infrastructure,  protocol management  and  database   support,  among  others,  4.29  million  family  farmers  with attributes.  In  the early  stages,  the software  can be used to replace  paper-based  reports with an online electronic  statements  and a simple diviation  analysis.